Changes in the N-Glycome, Glycoproteins with Asn-Linked Glycans, of Giardia lamblia with Differentiation from Trophozoites to Cysts - Ratner, Daniel M. (American Society for Microbiology (ASM), 2008)
Giardia lamblia is present in the intestinal lumen as a binucleate, flagellated trophozoite or a quadranucleate, immotile cyst. Here we used the plant lectin wheat germ agglutinin (WGA), which binds to the disaccharide di-N-acetyl-chitobiose (GlcNAc(2)), which is the truncated Asn-linked glycan (N-glycan) of Giardia, to affinity purify the N-glycomes (glycoproteins with N-glycans) of trophozoites and cysts. Fluorescent WGA bound to the perinuclear membranes, peripheral acidified vesicles, and plasma membranes of trophozoites. In contrast, WGA bound strongly to membranes adjacent to the wall of Giardia cysts and less strongly to the endoplasmic reticulum and acidified vesicles. WGA lectin-affinity chromatography dramatically enriched secreted and membrane proteins of Giardia, including proteases and acid phosphatases that retain their activities. With mass spectroscopy, we identified 91 glycopeptides with N-glycans and 194 trophozoite-secreted and membrane proteins, including 42 unique proteins. The Giardia oligosaccharyltransferase, which contains a single catalytic subunit, preferred N glycosylation sites with Thr to those with Ser in vivo but had no preference for flanking amino acids. The most-abundant glycoproteins in the N-glycome of trophozoites were lysosomal enzymes, folding-associated proteins, and unique transmembrane proteins with Cys-, Leu-, or Gly-rich repeats. We identified 157 secreted and membrane proteins in the Giardia cysts, including 20 unique proteins. Compared to trophozoites, cysts were enriched in Gly-rich repeat transmembrane proteins, cyst wall proteins, and unique membrane proteins but had relatively fewer Leu-rich repeat proteins, folding-associated proteins, and unique secreted proteins. In summary, there are major changes in the Giardia N-glycome with the differentiation from trophozoites to cysts.